Environmental consequences of the war on the urbanised territories of Ukraine - Kutkovyi, Denys (National Technical University "Kharkiv Polytechnic Institute", 2025)
The full-scale war in Ukraine has led to catastrophic changes in the environment. The environmental consequences of infrastructure destruction, soil and water pollution pose a serious threat to public health and ecosystems.
Keywords: war ecology; urbanised areas; infrastructure destruction; soil pollution; heavy metals; environmental safety; reclamation; sustainable development